Pathological study of the spleen in Hodgkin's disease - de Stefani, Eduardo; de los Santos, Julio; Fontán, Walter (Cirugía del Uruguay, 1972)
The authors refer the results obtained from the study of 22 splenectomy pieces obtained from patients suffering from Hodgkin's disease. Out of a total of 22 spleens, 13 -re.sected for the purpose of drawing up statisties- showed the characteristic lesions found in Hodgkin's disease. Macroscopic forms were divided into 4 categories: minodular, multinodular, confluent and miliary, according to the classification proposed by Ahmann et al for splenic lymphomas. Most fre- • quent macroscopic form was the multinodular type. There is a linear type relationshipo between the weight of the organ and the existence of Hodgkin-type lesions; an interesting aspect is that uninodular cases are found in spleens of normal weight. From the histological point of view . the majority of lesions correspond to the type known by thename of Lymphocitary Depletion. Finaly, the possible mechanisms leading to involvement of the spleen in Hodgkin's disease, are discussed.